2021
DOI: 10.1016/j.kint.2021.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Central and peripheral arterial diseases in chronic kidney disease: conclusions from a Kidney Disease: Improving Global Outcomes (KDIGO) Controversies Conference

Abstract: Chronic kidney disease (CKD) affects about 10% of all populations worldwide, with about 2 million people requiring dialysis. Although patients with CKD are at high risk of cardiovascular disease and events, they are often underrepresented or excluded in clinical trials, leading to important knowledge gaps about how to treat these patients. KDIGO (Kidney Disease: Improving Global Outcomes) convened the fourth clinical Controversies Conference on the heart, kidney and vasculature in Dublin, Ireland, in February … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 145 publications
(198 reference statements)
2
35
0
Order By: Relevance
“…40 In this analysis, we showed a similar baseline risk of a composite kidney outcome across those with and without PAD at baseline, with consistent relative and absolute reductions in the composite kidney outcome with canagliflozin treatment in those subgroups. 41 The clear benefits reported here are broadly consistent with a recent secondary analysis from the DECLARE-TIMI 58 trial, 19 where dapagliflozin was shown to reduce CV death, HHF, and progression of kidney disease in those with T2D, irrespective of PAD status at baseline. This study had similar inclusion criteria to the CANVAS Program.…”
Section: Discussionsupporting
confidence: 86%
“…40 In this analysis, we showed a similar baseline risk of a composite kidney outcome across those with and without PAD at baseline, with consistent relative and absolute reductions in the composite kidney outcome with canagliflozin treatment in those subgroups. 41 The clear benefits reported here are broadly consistent with a recent secondary analysis from the DECLARE-TIMI 58 trial, 19 where dapagliflozin was shown to reduce CV death, HHF, and progression of kidney disease in those with T2D, irrespective of PAD status at baseline. This study had similar inclusion criteria to the CANVAS Program.…”
Section: Discussionsupporting
confidence: 86%
“…HD superimposes additional cardiovascular risks under the cardiac burden of fluid overload due to pre-existing renal disease. The Kidney Disease: Improving Global Outcomes (KDIGO) conference discussed and made clinical recommendations for volume control ( Flythe et al, 2020 ), blood pressure management ( Cheung et al, 2021 ), and pathophysiological changes occurring in the vasculature of CKD patients in the CKD setting ( Johansen et al, 2021 ), and emphasized the necessity of timely hemodialysis for such patients. The guidelines also state that volume overload in patients with CKD leads to cardiac overload in these patients, making them more susceptible to cardiovascular disease, and therefore blood pressure and volume status are important modifiers of clinical outcomes in patients with CKD ( Flythe et al, 2015 ; Zoccali et al, 2017 ; Assimon et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The guidelines also state that volume overload in patients with CKD leads to cardiac overload in these patients, making them more susceptible to cardiovascular disease, and therefore blood pressure and volume status are important modifiers of clinical outcomes in patients with CKD ( Flythe et al, 2015 ; Zoccali et al, 2017 ; Assimon et al, 2018 ). Meanwhile the CKD environment accelerates the progression of central and peripheral arterial disease, especially the onset and progression of atherosclerosis ( Johansen et al, 2021 ).In HD conditions, the microinflammatory state underlying chronic kidney disease can be exacerbated by abnormalities in the immune system, complement activation triggered by blood contact with the dialysis membrane, accumulation of urotoxins and endotoxin translocation, accumulation of inflammatory factors due to decreased renal filtration capacity and local injury due to arteriovenous fistula formation. Inflammation acts as a catalyst for the development of cardiac insufficiency and contributes significantly to the development of cardiovascular complications in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with chronic kidney disease (CKD), including both non-dialysis-dependent and dialysis-dependent CKD, are at a high risk of stroke. [1][2][3][4][5] Stroke, however, has received less attention than heart disease in this patient population, 6 and at least three issues remain regarding the association between CKD and stroke, as discussed below.…”
Section: Introductionmentioning
confidence: 99%
“…First, the most frequently occurring stroke subtypes in patients with CKD and kidney failure are unclear. 6 A systematic review and meta-analysis found that ischaemic stroke was more frequent than haemorrhagic stroke among patients with non-dialysis-dependent CKD (defined as an estimated glomerular filtration rate [eGFR] <60 ml/min/1.73 m 2 ), but the proportion of ischaemic stroke decreased and was closer to that of haemorrhagic stroke among dialysis patients. 7 A question left unanswered by this meta-analysis is whether the frequency of ischaemic stroke decreases as eGFR decreases in non-dialysis-dependent CKD patients.…”
Section: Introductionmentioning
confidence: 99%